A preparation method and application of coal-based functional carbon material

By using coal-based functional carbon materials prepared by coal and hard carbon precursors, the problems of low energy density and high cost of the negative electrode materials of existing sodium ion batteries are solved, and sodium ions with high energy density, low cost and good cycle stability are achieved Battery negative electrode material.

CN117623274BActive Publication Date: 2025-02-25BEIJING UNIV OF CHEM TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311671426.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-07
Publication Date
2025-02-25
Estimated Expiration
2043-12-07

AI Technical Summary

Technical Problem

The existing sodium ion battery anode materials have low energy density, high cost, and complex preparation process, which limits the development of hard carbon anode.

Method used

Coal-based functional carbon material is used as the negative electrode material for sodium ion batteries, with coal as the main material, and a small part of hard carbon precursor is added, and a coal-based functional carbon material is prepared through mechanical mixing, crosslinking, pyrolysis and other steps.

Benefits of technology

It realizes a hard carbon negative electrode material with adjustable structure, simple process and high carbon yield. It has high energy density, low cost and good cycle stability, and is suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117623274B_ABST
    Figure CN117623274B_ABST
Patent Text Reader

Abstract

A method for preparing a coal-based functional carbon material and its application, which belongs to the field of negative electrode materials for alkali metal ion batteries. The polysaccharide molecules are modified by chemical reaction to synthesize a hard carbon precursor, and the coal and the hard carbon precursor are uniformly mixed, and then solid-phase heat treatment is performed to obtain a coal-based functional carbon material, which is applied to the negative electrode of a sodium ion battery. The negative electrode material has a high conductivity and a high molecular weight. ‑1 The current density of 1.547 W / m was 2.344 W / m, which showed a good sodium storage capacity of 313.97 mAh g ‑1 At the same time, the material has good cycle performance and extremely high first coulombic efficiency, and has the characteristics of simple production method, easy availability of raw materials, low cost, safety and environmental protection, which is conducive to the large-scale application of sodium ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of material design technology, and in particular to a method for synthesizing a coal-based functional carbon material and an application thereof in a sodium ion battery. Background Art

[0002] With the depletion of fossil energy and the increasing attention paid to environmental protection, renewable energy such as solar energy, wind energy, and tidal energy are playing an increasingly important role in energy utilization. Due to geographical location and traffic conditions, the further large-scale application of renewable energy is limited. Electrochemical energy storage represented by secondary batteries can store the electrical energy produced by renewable energy equipment in the form of chemical energy, and has the characteristics of convenient transportation and flexible application, which promotes the development of renewable energy.

[0003] Although lithium-ion batteries have the characteristics of high energy density and long stability, the production cost is increasing due to the increasing shortage of lithium metal resources. Sodium-ion batteries are gradually attracting people's attention due to the advantages of abundant sodium metal resources, uniform distribution and wide distribution. Since the energy density of sodium-ion batteries is lower than that of lithium-ion batteries, the development of high-energy-density, low-cost sodium-ion battery negative electrodes can further narrow the gap between the two and promote the commercial application of sodium-ion batteries.

[0004] The commercial negative electrode material for lithium-ion batteries is graphite, but this material is affected by thermodynamics in sodium-ion batteries and exhibits a low energy density that cannot meet the needs. Among the many types of negative electrode materials for alkali metal ion batteries, hard carbon materials have lower sodium storage potentials and higher reversible specific capacities, making them suitable as negative electrodes for sodium-ion batteries. Currently, the mainstream precursors for preparing hard carbon negative electrodes are biomass, sugars, phenolic resins, etc. The prices of these precursor materials are generally high, and the production process for preparing them into negative electrode materials is complex and the carbon yield is low, which limits the development of hard carbon negative electrodes. Summary of the invention

[0005] In order to overcome the deficiencies in the prior art, an embodiment of the present invention provides a method for synthesizing coal-based functional carbon materials and their application in sodium ion batteries. With coal, which is cheap and readily available as the main material, and a small amount of hard carbon precursor, a hard carbon negative electrode material with adjustable structure, simple method and high carbon yield is prepared. This material is very suitable as a negative electrode material for sodium ion batteries. This preparation method has sufficient raw materials, low cost, and simple process, which improves the high added value of coal and provides a feasible path for the synthesis of hard carbon negative electrodes for sodium ion batteries.

[0006] The technical solution adopted by the present invention is: a method for preparing a coal-based functional carbon material, which uses a carbon-based material and a hard carbon precursor as raw materials, mechanically mixes, presses into tablets, and then crosslinks and pyrolyzes them in an inert atmosphere; specifically, the method comprises the following steps:

[0007] (1) Dispersing biomass polysaccharides and vanillin in ethanol, stirring and heating under sealed conditions for 6-10 h; after filtering, dispersing with 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide in ethanol, stirring and heating under sealed conditions for 6-10 h, filtering and drying to obtain a hard carbon precursor;

[0008] The molar ratio of the biomass polysaccharide to vanillin is 1:(0.5-2.5); the molar ratio of the polysaccharide intermediate to 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is 1:(1-3);

[0009] (2) The carbon-based material and the hard carbon precursor are mechanically mixed and placed in a tube furnace, and an inert gas is pre-flowed; under the protection of the inert atmosphere, the temperature is raised to 400 o C-500 ℃, keep warm for 1-3h; continue to heat up to 800 o C-2200 ℃, keep warm for 1-3 h; after cooling, obtain coal-based functional carbon material;

[0010] The mass ratio of the coal to the hard carbon precursor is 9:(6-1).

[0011] The biomass polysaccharide includes one or a mixture of sucrose, chitin, chitosan, chitosan oligosaccharide, chitosan and cellulose.

[0012] The carbon-based material includes one or a mixture of lignite, bituminous coal, anthracite, coal tar, needle coke, petroleum asphalt, and petroleum coke.

[0013] The heating rates in step (2) are 3, 5, and 8 °C / min.

[0014] A method for preparing a vapor-deposited coal-based functional carbon material comprises placing the coal-based functional carbon material in a tubular furnace, heating the temperature to 700-800°C in an argon atmosphere, introducing a gas containing hydrocarbons, controlling the flow rate to 0.5-100 mL / min, and keeping the temperature for 40-60 minutes to deposit the hydrocarbons on the surface of the coal-based functional carbon material and cause cracking; after the vapor deposition is completed, the temperature is lowered to room temperature in an argon atmosphere to obtain the vapor-deposited coal-based functional carbon material.

[0015] The hydrocarbon-containing gas is a gas containing one or more of methane, benzene, ethylene, acetylene and propyne.

[0016] The coal-based functional carbon material is used in the negative electrode material of sodium ion batteries.

[0017] The vapor-deposited coal-based functional carbon material is applied to negative electrode materials of sodium ion batteries.

[0018] Furthermore, a method for preparing a coal-based functional carbon material comprises the following steps:

[0019] (1) Add polysaccharide and vanillin in a molar ratio of 1:(0.5-2.5) to the solvent ethanol for dissolution and mixing; heat to 60°C-90°C under sealed conditions, stir and react at a constant temperature for 0.5 h-10.5 h, and filter to obtain a polysaccharide intermediate;

[0020] The polysaccharide comprises one or more of sucrose, chitin, chitosan, chitosan oligosaccharide, chitosan and cellulose.

[0021] (2) adding the polysaccharide intermediate and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) into a solvent at a molar ratio of 1:(1-3) to dissolve and mix; raising the temperature to 60°C-90°C under sealed conditions, stirring at a constant temperature for 0.5 h-10.5 h, filtering and drying for 24 h to obtain a hard carbon precursor;

[0022] (3) Mechanically mixing coal and hard carbon precursor at a mass ratio of 1:(0-2) to obtain a mixed powder; loading the mixed powder into a porcelain boat and placing it into a tube furnace; heating the mixture to 400°C-500°C in an inert gas atmosphere, and keeping the temperature for 0.5-10 hours to allow the coal and hard carbon precursor to undergo a cross-linking reaction; the heating rate is 0.5-10°C / min.

[0023] The coal includes, but is not limited to, lignite, bituminous coal, anthracite, coal tar, needle coke, petroleum asphalt, one or a mixture of several of them.

[0024] (4) After the cross-linking reaction is completed, the temperature is further raised to 800°C-2200°C (heating rate is 0.5-10°C / min) under an inert gas atmosphere, and kept at this temperature for 0.5-10 h to cause a cracking reaction of the coal and polysaccharide mixed powder. After cooling, a coal-based functional carbon material is obtained.

[0025] In the present invention, vanillin is connected to the polysaccharide monomer side chain through the functional group through the reaction of polysaccharide and vanillin to form a polysaccharide intermediate, which is then reacted with DOPO to further expand the side chain to form a hard carbon precursor.

[0026] Preferably, the constant temperature stirring includes any one or more of a water bath, a sand bath, an oil bath, and a reaction kettle. The dissolving and mixing includes one or more of stirring, heating, and ultrasonic dispersion.

[0027] Preferably, the mechanical mixing includes any one or more of mechanical stirring, ball milling, grinding, and ultrasonic dispersion.

[0028] A negative electrode plate for a sodium ion battery, the negative electrode plate comprising:

[0029] A current collector, a binder coated on the current collector, conductive carbon black and the above-mentioned coal-based functional carbon material.

[0030] A secondary battery comprising the above-mentioned sodium ion battery negative electrode sheet. The use of the secondary battery is characterized in that the secondary battery is used for mobile equipment, electric-driven vehicles, hydropower generation, wind power generation, smart grid peak regulation, distributed power stations, backup power supplies or large-scale energy storage equipment for communication base stations.

[0031] The coal-based functional carbon material provided by the embodiment of the present invention has low raw material price, is safe and environmentally friendly, has high yield, and has a simple preparation process, and is suitable for industrial application. The material of the present invention is used as a negative electrode material for sodium ion batteries, and has the characteristics of high energy density, strong capacity retention ability, and good safety performance. The beneficial effects of the present invention are: a branch-rich hard carbon precursor is synthesized using polysaccharides, vanillin, and DOPO; the hard carbon precursor has greater steric hindrance than polysaccharides, regulates the structure of coal-based carbon materials, and improves the sodium storage capacity of coal-based carbon materials. Compared with other preparation processes for carbon negative electrode materials for sodium ion batteries, this process is simple, the raw material price is low, and it is conducive to industrialization. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The sodium ion battery in Example 2 at 50 mA·g -1 Charge and discharge curves under current density.

[0033] Figure 2 The sodium ion battery in Example 3 at 50 mA·g -1 Charge and discharge curves under current density.

[0034] Figure 3 The sodium ion battery in Example 4 at 50 mA·g -1 Charge and discharge curves under current density.

[0035] Figure 4 This is the XRD spectrum of the coal-based functional carbon material in Example 5.

[0036] Figure 5 The sodium ion battery in Example 5 at 50 mA·g -1 Charge and discharge curves under current density.

[0037] Figure 6 The sodium ion battery in Example 6 at 50 mA·g -1 Charge and discharge curves under current density.

[0038] Figure 7 The sodium ion battery in Example 7 at 50 mA·g -1 Charge and discharge curves under current density.

[0039] Figure 8 The sodium ion battery in Example 8 at 50 mA·g -1 Charge and discharge curves under current density.

[0040] Fig. 9 The sodium ion battery in Example 9 at 50 mA·g -1 Charge and discharge curves under current density.

[0041] Fig.10 The sodium ion battery in Example 10 at 50 mA·g -1 Charge and discharge curves under current density.

[0042] Fig.11 The sodium ion battery in Example 11 at 50 mA·g -1 Charge and discharge curves under current density.

[0043] Fig.12 The sodium ion battery in Example 1 is 50 mA·g -1 Charge and discharge curves under current density. DETAILED DESCRIPTION

[0044] The present invention is further described and illustrated in detail below through the accompanying drawings and examples, but it is not intended to limit the protection scope of the present invention. Example 1

[0045] Example 1 of the present invention provides a method for synthesizing a hard carbon precursor. The material is synthesized by chemical reaction of polysaccharide, vanillin and DOPO.

[0046] Dissolve 6.09 g of vanillin in 40 ml of anhydrous ethanol, add 5 g of chitosan, seal, heat in an oil bath at 80 °C for 8 h, and filter to obtain solid material A. Dissolve 8.83 g of DOPO in 40 ml of anhydrous ethanol, add solid powder A, seal, heat in an oil bath at 80 °C for 8 h, and dry for 24 h to obtain a hard carbon precursor. Example 2

[0047] Example 2 of the present invention provides a method for synthesizing a coal-based functional carbon material. The material is prepared from a hard carbon precursor and coal as raw materials, and is mechanically mixed, cross-linked, cured, and cracked under an inert atmosphere. The steps include:

[0048] 1.2 g of coal and 0.8 g of hard carbon precursor are mechanically mixed, evenly mixed and loaded into a porcelain boat and placed in a tubular furnace. Argon is pre-flowed for 0.5 h at room temperature to remove the air in the tube; the temperature is raised to 400 °C at a rate of 5 °C / min in an argon atmosphere and kept for 2 h to allow the coal and the hard carbon precursor to undergo a cross-linking reaction; after the cross-linking reaction is completed, the temperature is continued to be raised to 1200 °C at a rate of 5 °C / min in an argon atmosphere and kept for 2 h to allow further cracking reaction to occur; the sample is cooled to room temperature and taken out to obtain a coal-based functional carbon material, which is the negative electrode material for sodium ion batteries.

[0049] The coal-based functional carbon material prepared as above is used as the negative electrode material of the sodium ion battery to assemble the sodium ion battery.

[0050] Coal-based functional carbon material, carbon black, and sodium carboxymethyl cellulose were ground and mixed in a mass ratio of 8:1:1. After mixing evenly, an appropriate amount of deionized water was added to continue grinding into a slurry. The slurry was evenly coated on a copper foil with a scraper and vacuum dried at 80°C for 12 h, and then transferred to a glove box for standby use. The half-cell was assembled in an argon-filled glove box, with metallic sodium as the counter electrode and 1 mol of sodium trifluoromethanesulfonate dissolved in 1 L of diethylene glycol dimethyl ether as the electrolyte. The positive electrode shell, positive electrode sheet (sodium sheet), glass fiber separator, electrolyte, negative electrode sheet, and negative electrode shell were stacked in sequence and sealed with a sealing machine to complete the sodium ion battery assembly.

[0051] The assembled sodium ion battery was subjected to electrochemical charge and discharge tests with a test voltage range of 0.01 V-3 V. The test results are shown in Figure 1 The first discharge capacity is 328.85 mAh g -1 , the reversible specific capacity is 297.12 mAh g -1 The first coulombic efficiency is 90.35%, with good cycle stability. Example 3

[0052] A method for synthesizing a coal-based functional carbon material, wherein the material is prepared by mechanically mixing a hard carbon precursor and coal, cross-linking, curing, and cracking in an inert atmosphere, and the steps include:

[0053] 1.4 g of coal and 0.6 g of hard carbon precursor are mechanically mixed, evenly mixed and loaded into a porcelain boat and placed in a tubular furnace. Argon is pre-flowed for 0.5 h at room temperature to remove the air in the tube; the temperature is raised to 400 °C at a rate of 5 °C / min in an argon atmosphere and kept for 2 h to allow the coal and the hard carbon precursor to undergo a cross-linking reaction; after the cross-linking reaction is completed, the temperature is continued to be raised to 1100 °C at a rate of 5 °C / min in an argon atmosphere and kept for 2 h to allow further cracking reaction to occur; the sample is cooled to room temperature and taken out to obtain a coal-based functional carbon material, which is the negative electrode material for sodium ion batteries.

[0054] The carbon material prepared above was used as the active material of the battery negative electrode material for the preparation of sodium ion batteries, and electrochemical charge and discharge tests were performed. The preparation process and test method were the same as in Example 2. The test results are shown in Figure 2 , the reversible specific capacity is 270.52 mAh g -1 The first coulombic efficiency is 85.81%, with good cycle stability. Example 4

[0055] A method for synthesizing a coal-based functional carbon material, wherein the material is prepared by mechanically mixing a hard carbon precursor and coal, cross-linking, curing, and cracking in an inert atmosphere, and the steps include:

[0056] 1.4 g of coal and 0.6 g of hard carbon precursor are mechanically mixed, evenly mixed and loaded into a porcelain boat and placed in a tubular furnace. Argon is pre-flowed for 0.5 h at room temperature to remove the air in the tube; the temperature is raised to 400 °C at a rate of 5 °C / min in an argon atmosphere and kept for 2 h to allow the coal and the hard carbon precursor to undergo a cross-linking reaction; after the cross-linking reaction is completed, the temperature is continued to be raised to 1200 °C at a rate of 3 °C / min in an argon atmosphere and kept for 2 h to allow further cracking reaction to occur; the sample is cooled to room temperature and taken out to obtain a coal-based functional carbon material, which is the negative electrode material for sodium ion batteries.

[0057] The carbon material prepared above was used as the active material of the battery negative electrode material for the preparation of sodium ion batteries, and electrochemical charge and discharge tests were performed. The preparation process and test method were the same as in Example 2. The test results are shown in Figure 3 , the reversible specific capacity is 305.77 mAh g -1 The first coulombic efficiency is 91.27%, with good cycle stability. Example 5

[0058] A method for synthesizing a coal-based functional carbon material, wherein the material is prepared by mechanically mixing a hard carbon precursor and coal, cross-linking, curing, and cracking in an inert atmosphere, and the steps include:

[0059] 1.4 g of coal and 0.6 g of hard carbon precursor are mechanically mixed, evenly mixed and loaded into a porcelain boat and placed in a tubular furnace. Argon is pre-flowed for 0.5 h at room temperature to remove the air in the tube; the temperature is raised to 400 °C at a rate of 5 °C / min in an argon atmosphere and kept for 2 h to allow the coal and the hard carbon precursor to undergo a cross-linking reaction; after the cross-linking reaction is completed, the temperature is continued to be raised to 1200 °C at a rate of 5 °C / min in an argon atmosphere and kept for 2 h to allow further cracking reaction to occur; the sample is cooled to room temperature and taken out to obtain a coal-based functional carbon material, which is the negative electrode material for sodium ion batteries.

[0060] The carbon material prepared above was used as the active material of the battery negative electrode material for the preparation of sodium ion batteries, and electrochemical charge and discharge tests were performed. The preparation process and test method were the same as in Example 2. The test results are shown in Figure 5 , the reversible specific capacity is 313.97 mAh g -1 The first coulombic efficiency is 90.29%, with good cycle stability. Example 6

[0061] A method for synthesizing a coal-based functional carbon material, wherein the material is prepared by mechanically mixing a hard carbon precursor and coal, cross-linking, curing, and cracking in an inert atmosphere, and the steps include:

[0062] 1.4 g of coal and 0.6 g of hard carbon precursor are mechanically mixed, evenly mixed and loaded into a porcelain boat and placed in a tubular furnace. Argon is pre-flowed for 0.5 h at room temperature to remove the air in the tube; the temperature is raised to 500 °C at a rate of 5 °C / min in an argon atmosphere and kept for 2 h to allow the coal and the hard carbon precursor to undergo a cross-linking reaction; after the cross-linking reaction is completed, the temperature is continued to be raised to 1200 °C at a rate of 5 °C / min in an argon atmosphere and kept for 2 h to further undergo a cracking reaction; the sample is cooled to room temperature and taken out to obtain a coal-based functional carbon material, which is the negative electrode material for sodium ion batteries.

[0063] The carbon material prepared above was used as the active material of the battery negative electrode material for the preparation of sodium ion batteries, and electrochemical charge and discharge tests were performed. The preparation process and test method were the same as in Example 2. The test results are shown in Figure 6 , the reversible specific capacity is 291.55 mAh g -1 The first coulombic efficiency is 89.23%, with good cycle stability. Example 7

[0064] A method for synthesizing a coal-based functional carbon material, wherein the material is prepared by mechanically mixing a hard carbon precursor and coal, cross-linking, curing, and cracking in an inert atmosphere, and the steps include:

[0065] 1.4 g of coal and 0.6 g of hard carbon precursor are mechanically mixed, evenly mixed and loaded into a porcelain boat and placed in a tubular furnace. Argon is pre-flowed for 0.5 h at room temperature to remove the air in the tube; the temperature is raised to 400 °C at a rate of 5 °C / min in an argon atmosphere and kept for 2 h to allow the coal and the hard carbon precursor to undergo a cross-linking reaction; after the cross-linking reaction is completed, the temperature is continued to be raised to 1200 °C at a rate of 8 °C / min in an argon atmosphere and kept for 2 h to allow further cracking reaction to occur; the sample is cooled to room temperature and taken out to obtain a coal-based functional carbon material, which is the negative electrode material for sodium ion batteries.

[0066] The carbon material prepared above was used as the active material of the battery negative electrode material for the preparation of sodium ion batteries, and electrochemical charge and discharge tests were performed. The preparation process and test method were the same as in Example 2. The test results are shown in Figure 7 , the reversible specific capacity is 260.86 mAh g -1 The first coulombic efficiency is 90.45%, with good cycle stability. Example 8

[0067] A method for synthesizing a coal-based functional carbon material, wherein the material is prepared by mechanically mixing a hard carbon precursor and coal, cross-linking, curing, and cracking in an inert atmosphere, and the steps include:

[0068] 1.4 g of coal and 0.6 g of hard carbon precursor are mechanically mixed, evenly mixed and loaded into a porcelain boat and placed in a tubular furnace. Argon is pre-flowed for 0.5 h at room temperature to remove the air in the tube; the temperature is raised to 400 °C at a rate of 5 °C / min in an argon atmosphere and kept for 2 h to allow the coal and the hard carbon precursor to undergo a cross-linking reaction; after the cross-linking reaction is completed, the temperature is continued to be raised to 1300 °C at a rate of 5 °C / min in an argon atmosphere and kept for 2 h to allow further cracking reaction to occur; the sample is cooled to room temperature and taken out to obtain a coal-based functional carbon material, which is the negative electrode material for sodium ion batteries.

[0069] The carbon material prepared above was used as the active material of the battery negative electrode material for the preparation of sodium ion batteries, and electrochemical charge and discharge tests were performed. The preparation process and test method were the same as in Example 2. The test results are shown in Figure 8 , the reversible specific capacity is 290.11 mAh g -1 The first coulombic efficiency is 89.34%, with good cycle stability. Example 9

[0070] A method for synthesizing a coal-based functional carbon material, wherein the material is prepared by mechanically mixing a hard carbon precursor and coal, cross-linking, curing, and cracking in an inert atmosphere, and the steps include:

[0071] 1.6 g of coal and 0.4 g of hard carbon precursor are mechanically mixed, evenly mixed and loaded into a porcelain boat and placed in a tubular furnace. Argon is pre-flowed for 0.5 h at room temperature to remove the air in the tube; the temperature is raised to 400 °C at a rate of 5 °C / min in an argon atmosphere and kept for 2 h to allow the coal and the hard carbon precursor to undergo a cross-linking reaction; after the cross-linking reaction is completed, the temperature is continued to be raised to 1200 °C at a rate of 5 °C / min in an argon atmosphere and kept for 2 h to allow further cracking reaction to occur; the sample is cooled to room temperature and taken out to obtain a coal-based functional carbon material, which is the negative electrode material for sodium ion batteries.

[0072] The carbon material prepared above was used as the active material of the battery negative electrode material for the preparation of sodium ion batteries, and electrochemical charge and discharge tests were performed. The preparation process and test method were the same as in Example 2. The test results are shown in Fig. 9 , the reversible specific capacity is 288.60 mAh g -1 The first coulombic efficiency is 88.14%, with good cycle stability. Example 10

[0073] A method for synthesizing a coal-based functional carbon material, wherein the material is prepared by mechanically mixing a hard carbon precursor and coal, cross-linking, curing, and cracking in an inert atmosphere, and the steps include:

[0074] 1.8 g of coal and 0.2 g of hard carbon precursor are mechanically mixed, evenly mixed and loaded into a porcelain boat and placed in a tubular furnace. Argon is pre-flowed for 0.5 h at room temperature to remove the air in the tube; the temperature is raised to 400 °C at a rate of 5 °C / min in an argon atmosphere and kept for 2 h to allow the coal and the hard carbon precursor to undergo a cross-linking reaction; after the cross-linking reaction is completed, the temperature is continued to be raised to 1200 °C at a rate of 5 °C / min in an argon atmosphere and kept for 2 h to allow further cracking reaction to occur; the sample is cooled to room temperature and taken out to obtain a coal-based functional carbon material, which is the negative electrode material for sodium ion batteries.

[0075] The carbon material prepared above was used as the active material of the battery negative electrode material for the preparation of sodium ion batteries, and electrochemical charge and discharge tests were performed. The preparation process and test method were the same as in Example 2. The test results are shown in Fig.10 , the reversible specific capacity is 284.11 mAh g -1 The first coulombic efficiency is 90.58%, with good cycle stability. Embodiment 11

[0076] Take 1 g of the coal-based functional carbon material powder obtained in Example 2, put it into a porcelain boat and put it into a tubular furnace, pre-pass argon at room temperature for 0.5 h to remove the air in the tube; in an argon atmosphere, heat to 750 ° C at a rate of 10 ° C / min, pass a benzene-argon mixture, control the flow rate to 40 mL / min, and keep warm for 40 minutes to allow benzene molecules to deposit on the surface of the sample powder and crack; after the vapor deposition is completed, the argon atmosphere is cooled to room temperature to obtain a vapor-deposited coal-based functional carbon material, which is the negative electrode material for sodium ion batteries.

[0077] The carbon material prepared above was used as the active material of the battery negative electrode material for the preparation of sodium ion batteries, and electrochemical charge and discharge tests were performed. The preparation process and test method were the same as in Example 2. The test results are shown in Fig.11 , the first discharge capacity can reach 408.91 mAh g -1 , the reversible specific capacity is 303.97 mAh g -1 Compared with Example 2, the first discharge capacity and reversible capacity of the material after the vapor deposition treatment are improved. The use of benzene molecules for vapor deposition on the material surface can effectively reduce the pore size of the material and form a graphitized layer on the material surface, thereby increasing the sodium storage capacity.

[0078] Comparative Example 1

[0079] On the basis of Example 2, other conditions remain unchanged, and the hard carbon precursor is replaced with chitosan. The carbon material prepared above is used as the active material of the battery negative electrode material for the preparation of sodium ion batteries, and electrochemical charge and discharge tests are performed. The preparation process and test method are the same as in Example 2. The test results are shown in Fig.12 , the reversible specific capacity is 238.79 mAh g -1 The first coulombic efficiency is 89.82%, with good cycle stability.

[0080] The battery performance test results show that the coal-based functional carbon material provided by the present invention has excellent electrochemical properties. Due to the addition of the hard carbon precursor, it plays a role in regulating the molecular structure of coal, so that the coal-based functional carbon material has the advantages of high specific capacity, long cycle life and good rate performance as the negative electrode of the sodium ion battery.

Claims

1. A method for preparing a coal-based functional carbon material, characterized in that: The process is to use coal and hard carbon precursor as raw materials, mechanically mix, press into tablets, and then crosslink and pyrolyze them in an inert atmosphere. The process specifically includes the following steps: (1) Dispersing biomass polysaccharide and vanillin in ethanol, stirring and heating for 6-10 h under sealed conditions, filtering to obtain a polysaccharide intermediate, and dispersing the polysaccharide intermediate and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide in ethanol, stirring and heating for 6-10 h under sealed conditions, filtering and drying to obtain a hard carbon precursor; The molar ratio of the biomass polysaccharide to vanillin is 1:(0.5-2.5); the molar ratio of the polysaccharide intermediate to 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is 1:(1-3); (2) Mechanically mix the coal and the hard carbon precursor, place them in a tubular furnace, and pre-pass an inert gas; under the protection of the inert atmosphere, heat them to 400°C-500°C and keep them warm for 1-3 hours; continue to heat them to 800°C-2200°C and keep them warm for 1-3 hours; and obtain the coal-based functional carbon material after cooling; The mass ratio of the coal to the hard carbon precursor is 9:(6-1).

2. The method for preparing a coal-based functional carbon material according to claim 1, characterized in that: The biomass polysaccharide includes one or a mixture of sucrose, chitin, chitosan, chitosan oligosaccharide, chitosan and cellulose.

3. The method for preparing a coal-based functional carbon material according to claim 1, characterized in that: The coal includes one or a mixture of lignite, bituminous coal, anthracite, coal tar, needle coke, petroleum asphalt, and petroleum coke.

4. The method for preparing a coal-based functional carbon material according to claim 1, characterized in that: The heating rates in step (2) are 3, 5, and 8 °C / min.

5. A method for preparing a coal-based functional carbon material by vapor deposition, characterized in that: The coal-based functional carbon material prepared by any method of claims 1-4 is placed in a tubular furnace, heated to 700-800 ° C in an argon atmosphere, and a gas containing hydrocarbons is introduced, with a flow rate controlled at 0.5-100 mL / min. The mixture is kept warm for 40-60 minutes to allow the hydrocarbons to be deposited on the surface of the coal-based functional carbon material and cracked. After the vapor deposition is completed, the temperature is lowered to room temperature in the argon atmosphere to obtain a vapor-deposited coal-based functional carbon material.

6. The method for preparing a coal-based functional carbon material by vapor deposition according to claim 5, characterized in that: The hydrocarbon-containing gas is a gas containing one or more of methane, benzene, ethylene, acetylene and propyne.

7. Application of the coal-based functional carbon material prepared by the method according to any one of claims 1 to 4, characterized in that: The coal-based functional carbon material is used in the negative electrode material of sodium ion batteries.

8. Application of the vapor-deposited coal-based functional carbon material prepared by the method according to claim 5 or 6, characterized in that: The vapor-deposited coal-based functional carbon material is applied to negative electrode materials of sodium ion batteries.

Citation Information

Patent Citations

  • Middle-pore carbon material and its preparation method

    CN102923687A

  • Sodion secondary battery negative electrode material and preparing method and application thereof

    CN105185997A